Presence of corrective saccades in patients with normal vestibulo-ocular reflex gain in video head impulse test - Kabaya, Kayoko; Fukushima, Akina; Katsumi, Sachiyo; Minakata, Toshiya; Iwasaki, Shinichi (Frontiers in Neurology, 2023)
Background The video head impulse test (vHIT) is a valuable clinical tool that can help identify dysfunction of the semicircular canals. While in cases with semicircular canal dysfunction, both decreased vestibulo-ocular reflex (VOR) gain and corrective saccades (CS) are usually observed, there are cases which show CS despite normal VOR gain in vHIT. Objective This study aimed to investigate the clinical characteristics of patients who showed CS with normal VOR gain in vHIT. Materials and methods Among 390 patients who underwent vHIT, 51 patients (20 males and 31 females, age 31–87 years, average 61.3 years old) who showed CS with normal VOR gain unilaterally during horizontal vHIT were included. All patients had normal vHIT (normal VOR gain and absent CS) on the contralateral side. The VOR gain of vHIT, the maximum slow phase velocity in the caloric test, and the amplitude of cervical and ocular vestibular evoked myogenic potentials (cVEMPs and oVEMPs) were analyzed. Results The VOR gain on the affected side (0.95 ± 0.08) was significantly smaller than that on the contralateral side (1.03 ± 0.13) in horizontal vHIT (p < 0.001). The maximum slow phase velocity in the caloric test on the affected side (17.9 ± 17.8 degrees/s) was significantly smaller than that on the contralateral side (21.3 ± 16.6 degrees/s, p = 0.020). There were no significant differences in the amplitude of cVEMPs or oVEMPs between the affected side and the contralateral side (p = 0.096 for cVEMP; p = 0.770 for oVEMP). Conclusion The side that showed CS with normal VOR gain in horizontal vHIT showed significantly smaller VOR gain as well as smaller caloric responses compared to the contralateral side. Having CS with normal VOR gain could be a sensitive indicator of mild dysfunction of the semicircular canals.